Análise elementar de carnes: desenvolvimento de métodos analíticos e estratégias para técnicas com fonte de plasma - Silva, Ana Beatriz Santos da (Universidade Federal de São Carlos, 2020)
Meat is widely consumed around the world. Besides, this food has a significant influence on the Brazilian economy. Regarding the nutritional terms, it is considered as a source of essential elements (e.g., molybdenum, copper, and manganese) that are important to the human organism. In this context, this thesis's goal is the development of analytical methods and the investigation of strategies for the determination of essential and toxic elements in meat by microwave-induced plasma optical emission spectrometry (MIP OES) and inductively coupled plasma – Tandem mass spectrometry (ICP-MS/MS). The use of MIP OES was investigated for the determination of phosphorus from phospholipids in meat. Due to the introduction of organic solvent, some strategies were adopted, such as the employment of an external gas control module (EGCM) and the signal correction applying internal standardization (Te) and molecular species (OH). The accuracy was estimated by comparing the results obtained with ion chromatography. The recovery found using the internal standardization was 95%, while molecular specie was 94%. These results indicated that these signal corrections were effective, and their employment significantly improved accuracy. The dispersive liquid-liquid microextraction (DLLME) was used to enhance the procedure’s sensitivity for the determination of molybdenum in meat by MIP OES. In this study, the selection of extracting and dispersing solvents was based on the mixture design. Additionally, the DLLME parameters were optimized by applying a Box-Behnken design. A bovine liver certified reference material (1577c, NIST) was employed to check the accuracy and a recovery of 92% was obtained. The enhancement factor and the limit of detection estimated were 4.5 and 0.20 µg g-1, respectively. In another work, a critical evaluation of nebulizer effects in a nitrogen plasma was performed. Four nebulizers (concentric, MiraMist, OneNeb series 1 and 2) were investigated concerning the plasma fundamental parameters (e.g., temperature and number of electron density) and solvent transport efficiency. Besides, the reproducibility was evaluated in different matrices, and the accuracy was investigated by analyzing four CRMs and s spiked sample from sugarcane spirit due to its alcoholic composition. The results demonstrated that the plasma fundamental parameters were considerably affected by the nebulizer type. Besides, the OneNeb series 2 showed the best performance considering the sensitivity, solvent transport efficiency and precision. The determination of nine essential and toxic elements (As, Cd, Co, Cr, Mn, Mo, Pb, Sr, and V) in meat samples was performed by ICP-MS/MS. Initially, the use of gases (O2, H2, and He) in the reaction octopolar system (ORS) was explored to minimize the spectral interferences. The best operating mode was selected evaluating the recoveries obtained during the CRM analysis (1577b, NIST). For Cd, Co, Mo, Pb, and V, the ORS's gas use was not required. On the other hand, for chromium and arsenic, He was more suitable, and for Sr, H2 was the best. The limit of detection varied from 0.08 µg kg-1 (Cd) to 16 µg kg-1 (Mo). Then, meat samples were digested and analyzed by ICP-MS/MS using the optimal conditions. A correlation graphic showed the occurrence of a positive correlation between Cd – Pd and Sr – Pb.
Elemental analysis of meat: analytical methods development and strategies for the use of plasma-based techniques
Keywords: Carne; Análise de traços; MIP OES; Meat; Trace analysis; Plasma-based techniques; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE